(untitled) (Prostor, 2024)
The article examines the interior of school learning space in the German-speaking and southern part of the Nordic region from the 19th century to the present day. Through the review of sources, analysis of primary sources, and images, school learning space has been explored in relation to established pedagogical paradigms, Herbartian and Reform Paradigms, in terms of how they perceive teaching and learning process. In the 19th century, in line with a standardized teaching process, school learning space was relatively simply organised, with an orderly structure and rows of desks. With the emergence of Reform educators at the turn of the 19th to the 20th century, with a focus on teaching that catered to the needs and interests of students, school learning space acquired multiple roles and became the basis for the current understanding of school learning space. In Dewey’s concept of ideal school, a conceptual origin of modern architectural designs of school learning space can be recognised. Based on the analysis of these designs from the perspective of current trends, particularly communication pedagogy, it can be concluded that a constructive school learning space requires an open area that does not isolate students. Open questions for further research into school space have been indicated.